Analisis Pengaruh Media Sosial Dan Kualitas Pelayanan terhadap Keputusan Pembelian pada Angkringan Beranda Kali di Boja Kendal - Harlinda Mutia Dewi; Pemilia Sulistyowati (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2023)
This study aims to determine how the influence of social media and service quality on purchasing decisions. The population in this study were all consumers at the Beranda Kali angkringan. The strategy used in this study uses an associative research strategy using a quantitative descriptive approach because the research model built is causal. Researchers used a questionnaire as a data collection tool. This research was measured by a Likert Scale with the answers to each instrument item having a gradation from very positive to very negative.